Biological evaluation of 1, 2, 3‐triazole‐based polymers for potential applications as hard tissue material. Issue 16 (25th May 2015) - Pretzel, David; Sandmann, Benedict; Hartlieb, Matthias; Vitz, Jürgen; Hölzer, Stefan; Fritz, Nicole; Moszner, Norbert; Schubert, Ulrich S.
<x xml:space="preserve">Abstract</x> This contribution deals with the synthesis and subsequent bulk polymerization of multifunctional electron‐deficient internal alkynes with several multifunctional azides in a metal‐free 1, 3‐dipolar azide–alkyne cycloaddition. The biocompatibility of alkynes, azides, and resulting networks was investigated in a cell biological study. All monomers revealed distinctive concentration‐dependent cytotoxic properties. These harmful side effects on the cell integrity were completely diminished after polymerization of the educts resulting in materials with highly biocompatible properties.